THE CEREMONY BUKA LUWUR SUNAN KUDUS IN THE PERSPECTIVE OF THE STUDY OF ISLAMIC CULTURE - Farichatul Maftuchah; Sidik Fauji (IBDA` : Jurnal Kajian Islam dan Budaya, 2020)
The teachings of Islam come from a single source, God the Al- mighty. However, the application of Islam in people’s lives has become very diverse because of the interaction between these teachings with the local culture and traditions of the adherents. The differences and diver- sity that arise in the practices of Islamic teachings, if not treated prop- erly, can lead to blaming other people’s practices of Islamic teachings. Buka Luwur Ceremony is a culture in the Kudus area, Central Java, which has interacted with Islamic values. Buka Luwur Ceremony aims to pray for the spirit of Sunan Kudus, and at the same time to commemorate his services for successfully spreading Islam in Kudus area. In addition, it is also intended to model the success of Sunan Kudus in laying the founda- tion in preaching. In Islamic teaching perspective, Buka Luwur ceremony is full of Islamic and cultural values relevant to be applied in the midst of radicalism. Buka Luwur ceremony is able to unite two different prin- ciples between Islam and the culture/traditions of society.